2016
DOI: 10.1039/c6cp03464k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular self-healing mechanisms between C60-fullerene and anthracene unveiled by Raman and two-dimensional correlation spectroscopy

Abstract: The self-healing polymer P(LMA-co-MeAMMA) crosslinked with C60-fullerene has been studied by FT-Raman spectroscopy in combination with two-dimensional (2D) correlation analysis and density functional theory calculations. To unveil the molecular changes during the self-healing process mediated by the Diels-Alder equilibrium between 10-methyl-9-anthracenyl groups and C60-fullerene different anthracene-C60-fullerene adducts have been synthesized and characterized by time-, concentration- and temperature-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
(115 reference statements)
1
15
0
Order By: Relevance
“…Nevertheless, the temperature of the rDA reaction cannot be determined by this method, because this transition is not visible in the heating curves. Therefore, this behavior was examined (for CP2F) using FT‐Raman spectroscopy and two‐dimensional correlation analysis in a separate study . The study revealed two pronounced jumps (at 35 and 55 °C) in the Raman peak area for the signals of the anthracene and anthracene‐C 60 ‐fullerene adduct moieties and that the strongest change in these signals starts at 60 °C.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Nevertheless, the temperature of the rDA reaction cannot be determined by this method, because this transition is not visible in the heating curves. Therefore, this behavior was examined (for CP2F) using FT‐Raman spectroscopy and two‐dimensional correlation analysis in a separate study . The study revealed two pronounced jumps (at 35 and 55 °C) in the Raman peak area for the signals of the anthracene and anthracene‐C 60 ‐fullerene adduct moieties and that the strongest change in these signals starts at 60 °C.…”
Section: Resultssupporting
confidence: 65%
“…The band assignments of the monomers (AMMA and MAMMA), copolymers (P1 and P2) as well as fullerene‐containing copolymers (CP1F and CP2F) were depicted in Table S2. Previously, we investigated the self‐healing temperatures as well as the reversibility of CP2F by using Raman and two‐dimensional correlation spectroscopy . In this study, the rebounding behavior of the system in bulk was investigated revealing a stepwise degradation mechanism of anthracene‐C 60 ‐fullerene adducts over a large temperature range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,34] The use of sophisticated spectroscopic methods, such as CARS microscopy,t os tudy molecular processes during self-healing will lead to an improvement of self-healing materials as well as to a better understanding of the self-healing process and the mechanochemical activation of materials in general. [20,34] The use of sophisticated spectroscopic methods, such as CARS microscopy,t os tudy molecular processes during self-healing will lead to an improvement of self-healing materials as well as to a better understanding of the self-healing process and the mechanochemical activation of materials in general.…”
Section: Discussionmentioning
confidence: 99%
“…We expect the presented approach of simultaneously acquiring morphological and molecular information to be broadly applicable in the fieldo fs elf-healingm aterials to study for example,o ther self-healing reactions with dynamic covalent bonds like, for example, the Diels-Alder reactions. [20,34] The use of sophisticated spectroscopic methods, such as CARS microscopy,t os tudy molecular processes during self-healing will lead to an improvement of self-healing materials as well as to a better understanding of the self-healing process and the mechanochemical activation of materials in general.…”
Section: Discussionmentioning
confidence: 99%